Wisata Minat Khusus sebagai Alternatif Pengembangan Pariwisata di Kabupaten Bangli - I Wayan Wiwin (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2017)
The special interest tourism has become the current tourism trend where special interest tourism is done to avoid mass tourism in other words special interest tourism is one of an alternative tourism. Special interest tourism that became a new phenomenon in the world of tourism became one of the demands for the providers of tourist services. The motivation of tourists in findingsomething new and having a quality tourist experience leads to increased demand for special interest tourists. Bangli regency is one of the areas in Bali that has a diverse range of potential tourist attractions of special interest, such as: Bali Woso Camp Agro and Culture, The Ayodya Oemah Strawberry, Anjungan Tukad Melangit (ATM) Antugan, N’jung Bali Camp Songan, Tukad Cepung Waterfall, and Twin Hill Bunutin.